2002
DOI: 10.1016/s1470-0328(02)00124-6
|View full text |Cite
|
Sign up to set email alerts
|

Urinary and faecal incontinence following delayed primary repair of obstetric genital fistula

Abstract: Objective To evaluate: (1) the factors associated with the development of obstetric genitourinary fistula, (2) the incidence of urinary and faecal incontinence following closure of the fistula and (3) the urodynamic findings in women with persistent urinary incontinence. Design An observational clinical study.Setting A specialised fistula unit in a developing country.Population Women following successful anatomical closure of obstetric genitourinary fistula.Methods Fifty-five women were enrolled from the Fistu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 8 publications
(18 reference statements)
1
13
0
Order By: Relevance
“…Community‐based follow up of women who have undergone fistula repair surgery has been stated to be extremely difficult 4,6–8 . To the best of our knowledge, only one previous study have succeeded in such follow up 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Community‐based follow up of women who have undergone fistula repair surgery has been stated to be extremely difficult 4,6–8 . To the best of our knowledge, only one previous study have succeeded in such follow up 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite many reports on the primary closure rates of fistula surgery, 3–5 there is a paucity of data on long‐term outcomes following fistula repair, in particular a lack of data on urinary symptoms, reproductive health and quality of life among the treated populations. Reasons cited for this lack of population‐based follow up include the remote and inaccessible residence of most women with fistula, poor roads, the lack of telephones and postal services, and the relatively high cost of traveling 4,6–8 …”
Section: Introductionmentioning
confidence: 99%
“…In an uncontrolled observational study, 55% of women reported persistent urinary incontinence after surgery, while 38% reported altered fecal continence [7]. …”
Section: Introductionmentioning
confidence: 99%
“…Subsequent writers have cast doubt on Sims' claims of complete cure, and it may be that, although the fistulous opening was healed, bladder function remained compromised — even after modern fistula surgery, stress and urge incontinence can be problems 12 . ‐ 15 However, there is no doubt that Sims had made great progress in the understanding and techniques of fistula repair (Box 4).…”
Section: Sims and Fistula Repairmentioning
confidence: 99%